A detailed investigation of the applicability and utility of simulation and gaming in the teaching of civil engineering students - Long, Gavin (2010)
This thesis describes research carried out into the use of computer based simulations and games in learning and with particular regard to the education of engineering students. Existing research within the scope of the subject domain was fully reviewed and documented and a list of research aims and objectives were devised. It was identified that the use of educational simulation games (a hybrid combining aspects of simulation, games design and educational content) showed potential for the teaching of organisational and project management skills.